The Jaw-Locking Case of a Missed Tetanus Booster - Erica Westlake; Katherine Billings; Ann McMoran; Katherine Selman; Sarab Sodhi (Clinical Practice and Cases in Emergency Medicine)
Introduction: Tetanus is a now rare disease due to the widespread administration of scheduled and prophylactic vaccines, making it exceptionally uncommon to appear in many emergency departments. Clinical suspicion alone is used to make the diagnosis as there are currently no immediately available diagnostic tests available to the clinician. If left unrecognized and untreated, however, tetanus can lead to airway compromise and death. Case Report: We report a case of a young male who presented to the emergency department with intermittent full body spasms and stiffness of the masseter muscles in the setting of recent assaults and lacerations weeks prior who had not received tetanus since 2008. Immediate calls were placed to infectious disease consultants and the patient was treated with intravenous immunoglobulin, tetanus immunization, metronidazole, and ceftriaxone. Further work up revealed rhabdomyolysis, elevated lactate, and unremarkable imaging. Conclusion: Following treatment, the patient’s symptoms improved to resolution with completion of therapy, effectively confirming the diagnosis of tetanus.